Adavosertib plus gemcitabine for platinum-resistant or platinum-refractory recurrent ovarian cancer: a double-blind, randomised, placebo-controlled, phase 2 trial. Issue 10271 (23rd January 2021) - Lheureux, Stephanie; Cristea, Mihaela C; Bruce, Jeffrey P; Garg, Swati; Cabanero, Michael; Mantia-Smaldone, Gina; Olawaiye, Alexander B; Ellard, Susan L; Weberpals, Johanne I; Wahner Hendrickson, Andrea E; Fleming, Gini F; Welch, Stephen; et al.
Summary: Background: The Wee1 (WEE1hu) inhibitor adavosertib and gemcitabine have shown preclinical synergy and promising activity in early phase clinical trials. We aimed to determine the efficacy of this combination in patients with ovarian cancer. Methods: In this double-blind, randomised, placebo-controlled, phase 2 trial, women with measurable recurrent platinum-resistant or platinum-refractory high-grade serous ovarian cancer were recruited from 11 academic centres in the USA and Canada. Women were eligible if they were aged 18 years or older, had an Eastern Cooperative Oncology Group performance status of 0–2, a life expectancy of more than 3 months, and normal organ and marrow function. Women with ovarian cancer of non-high-grade serous histology were eligible for enrolment in a non-randomised exploratory cohort. Eligible participants with high-grade serous ovarian cancer were randomly assigned (2:1), using block randomisation (block size of three and six) and no stratification, to receive intravenous gemcitabine (1000 mg/m 2 on days 1, 8, and 15) with either oral adavosertib (175 mg) or identical placebo once daily on days 1, 2, 8, 9, 15, and 16, in 28-day cycles until disease progression or unacceptable toxicity. Patients and the team caring for each patient were masked to treatment assignment. The primary endpoint was progression-free survival. The safety and efficacy analysis population comprised all patients who received at least one dose of treatment. The trial is registered with ClinicalTrials.gov, NCT02151292, and is closed to accrual. Findings: Between Sept 22, 2014, and May 30, 2018, 124 women were enrolled, of whom 99 had high-grade serous ovarian cancer and were randomly assigned to adavosertib plus gemcitabine (65 [66%]) or placebo plus gemcitabine (34 [34%]). 25 women with non-high-grade serous ovarian cancer were enrolled in the exploratory cohort. After randomisation, five patients with high-grade serous ovarian cancer were found to be ineligible (four in the experimental group and one in the control group) and did not receive treatment. Median age for all treated patients (n=119) was 62 years (IQR 54–67). Progression-free survival was longer with adavosertib plus gemcitabine (median 4·6 months [95% CI 3·6–6·4] with adavosertib plus gemcitabine vs 3·0 months [1·8–3·8] with placebo plus gemcitabine; hazard ratio 0·55 [95% CI 0·35–0·90]; log-rank p=0·015). The most frequent grade 3 or worse adverse events were haematological (neutropenia in 38 [62%] of 61 participants in the adavosertib plus gemcitabine group vs ten [30%] of 33 in the placebo plus gemcitabine group; thrombocytopenia in 19 [31%] of 61 in the adavosertib plus gemcitabine group vs two [6%] of 33 in the placebo plus gemcitabine group). There were no treatment-related deaths; two patients (one in each group in the high-grade serous ovarian cancer cohort) died while on study medication (from sepsis in the experimental group and from disease progression in the control group). Interpretation: The observed clinical efficacy of a Wee1 inhibitor combined with gemcitabine supports ongoing assessment of DNA damage response drugs in high-grade serous ovarian cancer, a TP53 -mutated tumour type with high replication stress. This therapeutic approach might be applicable to other tumour types with high replication stress; larger confirmatory studies are required. Funding: US National Cancer Institute Cancer Therapy Evaluation Program, Ontario Institute for Cancer Research, US Department of Defense, Princess Margaret Cancer Foundation, and AstraZeneca.